The Role of Melinjo Cracker MSMEs in Boosting the Local Economy in Serambingan Village, Batu Bara Regency an Islamic Economic Perspective - Rani Maylani; Khairina Tambunan; Rahmi Syahriza (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the role of the emping melinjo (melinjo chips) MSME in improving the economy of the Serambingan Village community, Batu Bara Regency, and examine its business practices from an Islamic economic perspective. The study employed a qualitative field research approach through observation, in-depth interviews, and documentation of the predominantly female entrepreneurs, run from generation to generation using simple equipment. The results indicate that the emping melinjo MSME contributes significantly to family income (Rp 300,000–Rp 1,000,000 per month), particularly for female heads of households and laborer/farmer families. The production process remains traditional and dependent on weather, raw material availability, and the physical limitations of the elderly entrepreneurs. From an Islamic economic perspective, these business practices reflect the values ​​of honesty, hard work, and the halal utilization of local resources, which align with the principles of maqasid al-Shariah. The findings also reveal that the income generated from this business contributes to household welfare and the fulfillment of family needs, demonstrating the practical implementation of maqashid al-Shariah. The study recommends strengthening sup port through marketing innovation, improving work ergonomics, and Islamic social finance interventions to increase the capacity and sustainability of MSMEs.